Wire rod for annealing-free, high-hardenability, high-strength fasteners and manufacturing method thereof
By adding specific elements to the steel for fasteners and controlling the microstructure, a high-hardening and high-strength fastener strip without annealing was designed, which solved the problem of annealing of the steel for fasteners in the prior art. , achieving both high hardenability and high strength, simplifying the production process and reducing costs.
Patent Information
- Application Number
- CN202210059035.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-01-19
AI Technical Summary
The existing steel for fasteners has a fast cooling speed during the production process of conventional high-speed wires, which leads to annealing for subsequent cold deformation processing. The process flow is long and does not meet the requirements of environmentally friendly production processes. At the same time, the hardenability and strength of steel for high-hardenability and high-strength fasteners are difficult to meet the needs of fasteners of 8.8 or above without annealing.
By adding elements such as C, Mn, Cr to the chemical composition of the steel for fasteners, and controlling Ti/N≥3.5 and Mn+Cr≥1.10%, a fastening of ferrite + pearlite was designed to be designed The plates for parts adopt a lower rolling temperature, wire spinning temperature, and sectional post-rolling cooling method to control the tensile strength of the plates ≤650MPa to achieve high hardenability and high strength without annealing.
The obtained fastener strip has high hardenability, J11 hardenability ≥40HRC, and J15 hardenability ≥33HRC, which can meet the quenching requirements of fasteners of grade 8.8 and above, and can be used directly for pulling without annealing. The transformation and transformation simplifies the production process and reduces production costs.
Smart Images

Figure BDA0003477379800000091 
Figure BDA0003477379800000101 
Figure BDA0003477379800000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steel for fasteners, and particularly relates to a wire rod for annealing-free, high-hardenability and high-strength fasteners and a manufacturing method thereof. Background Art
[0002] Threaded and bolted connections are one of the most common connection methods between automobile and mechanical parts. Threaded connections have the advantages of easy disassembly and assembly, simple structure, and reliable connection. According to the national standard GB / T 3098.1 "Mechanical properties of fasteners bolts, screws and studs", the commonly used fasteners are mostly 4.6-12.9 grades (equivalent to 400MPa-1200MPa tensile strength level). According to the national standard GB / T 6478 "Steel for cold heading and cold extrusion", the steel types include carbon steel, carbon boron steel, medium-low carbon low alloy steel, medium-low carbon alloy steel and other types. Usually, bolts below grade 6.8 are mostly rolled from low carbon steel series wire rods and do not require heat treatment; grades 8.8-12.9 are generally made of medium carbon, low alloy steel, and medium carbon alloy steel series after quenching and tempering heat treatment. For the series that require quenching and tempering heat treatment, considering the stress concentration and cracking tendency that may be caused by quenching, parts below M12 are usually quenched by water cooling, and parts above M12 are quenched by oil cooling.
[0003] Chinese patent CN108913992 discloses "a steel for bolts and its application". The chemical composition of the steel is as follows: C: 0.25-0.33%, Si: 0.1-0.6%, Mn: 1.3-1.7%, P≤0.035%, S≤0.035%, Ti: 0.04-0.10%, B: 0.0008-0.0035%, Al: 0.02-0.2%, Cu≤0.5%, Ni≤0.5%, and also contains Cr: 0.02-1%, Mo: 0.002-0.25%, V: 0.1-0.3%, Nb: 0.015-0.06%, and the mass ratio of molybdenum, vanadium and niobium is 1:1.2:0.24. This patent also stipulates that the wire of the steel with the above composition is only subjected to wire drawing and cold heading when producing 8.8-grade bolts, and does not need to go through a heat treatment process; when producing 12.9-grade bolts, the wire must be spheroidized, descaled, wire drawn, cold headed, quenched, and tempered, which is a typical method for manufacturing quenched and tempered heat-treated bolts. However, the specific manufacturing method of the hot-rolled wire and the key process control method are not described, and it is difficult to obtain annealing-free hot-rolled wire through conventional hot rolling processes.
[0004] Chinese patent CN105543678 discloses "a boron-containing high-strength anneal-free fastener steel wire rod and its preparation method". The chemical composition of the steel is as follows: C: 0.20-0.24%, Si≤0.04%, Mn: 0.50-0.70%, Cr: 0.25-0.35%, Ti: 0.035-0.055%, Als: 0.035-0.055%, B: 0.0045-0.0060%, S≤0.004%, P≤0.012%, O≤0.0015%, H≤0.00015%, and the rest is Fe and unavoidable impurities. It also stipulates the detailed operations of molten iron pretreatment desulfurization, molten steel smelting, deoxidation alloying, molten steel LF furnace refining, molten steel VD furnace vacuum refining, molten steel casting, billet heating, controlled rolling and controlled cooling. Among them, the size of the molten steel casting billet is 150×150mm, and the cross-sectional size is relatively small. When rolling larger-sized wire rods above 25mm, the microscopic defects in the billet are not easy to eliminate; the heating temperature of the billet is 1080-1120℃, which is prone to produce adverse effects such as surface decarburization and grain growth during high-temperature heating and rolling. The role of each alloy element and the applicable part size specifications are not explained.
[0005] Chinese patent CN103695774A discloses "a kind of high-strength fastener steel with low hardness and hot-rolled titanium and boron, and its production method", and its production process includes the following steps: (1) LF refining: under the condition of ensuring good deoxidation of molten steel and slag, first add titanium alloy, weakly stir for 3 minutes and then add ferroboron, and control the N mass fraction below 55ppm; (2) rolling process: rolling in the recrystallization zone of the steel grade, the temperature control range is: the temperature of the steel billet in the heating furnace is 1080-1180℃, the rolling start temperature is 980-1100℃, the wire laying temperature is 860-970℃, the roller inlet speed is 0.2-0.35m / s, and the coiling temperature is 600-630℃. The wire heating temperature disclosed in this patent is relatively high, which is easy to produce adverse effects such as surface decarburization and grain growth during high-temperature heating and rolling, and does not meet the requirements of low-temperature green environmental protection.
[0006] With the introduction of environmental protection requirements such as energy conservation and emission reduction, carbon peak and carbon neutrality, as well as the development of various production sectors such as automobiles, machinery, construction, and light industry, low-cost requirements have been put forward for the materials used to manufacture various fasteners (bolts, screws, nuts, etc.) in the production of raw materials, processing and manufacturing. However, in the existing technology, in the conventional high-speed wire production process, the cooling speed of high-hardenability and high-strength fastener steel is relatively fast under the conventional cooling process, and the hot-rolled wire rods usually have high strength. The user end usually needs to undergo annealing before subsequent cold deformation processing, and the process flow is relatively long, which does not meet the requirements of environmentally friendly production processes.
[0007] In the prior art, however, the steel used for fasteners that does not require annealing is usually low-carbon carbon steel, which has a low content of alloy elements including carbon and low hardenability. It is usually used to produce low-strength 4.8 and 6.8 (400MPa and 600MPa) fasteners, and cannot be used to produce fasteners above 8.8. Summary of the invention
[0008] The object of the present invention is to provide an annealing-free high-hardenability high-strength wire rod for fasteners and a manufacturing method thereof. The wire rod for fasteners has high hardenability, J11 hardenability ≥40HRC, J15 hardenability ≥33HRC, can meet the quenching requirement of 50% martensite in the core of parts with a diameter of less than M32, and can be used to manufacture fasteners of grade 8.8 and above; at the same time, the fastener wire rod has low tensile strength, tensile strength ≤650MPa, and can be directly used for drawing and modification, eliminating a time-consuming and energy-intensive annealing process on the client side, simplifying the production process of fasteners and reducing production costs.
[0009] To achieve the above object, the technical solution of the present invention is:
[0010] A wire rod for annealing-free, high-hardenability and high-strength fasteners, the chemical composition mass percentage of which is: C: 0.19-0.39%, Si≤0.25%, Mn: 0.6-1.45%, Cr: 0.05-0.99%, Al: 0.010-0.035%, S≤0.005%, B: 0.001-0.004%, Ti: 0.01-0.15%, O: 0.0005-0.0030%, N: 0.001-0.007%, and the rest is Fe and other unavoidable impurities, and it is also necessary to meet the following requirements at the same time:
[0011] Ti / N ≥ 3.5;
[0012] Mn+Cr≥1.10%.
[0013] The microstructure of the wire rod for fasteners of the present invention is ferrite + pearlite, and the ferrite content is 51-77%, and the thickness of the ferrite-cementite layer in the pearlite ranges from 150 to 400 nm.
[0014] The wire rod for fasteners of the present invention has a hardenability of J11 ≥40HRC, a hardenability of J15 ≥33HRC, and a tensile strength of ≤650MPa.
[0015] In the composition design of the wire rod for fasteners of the present invention:
[0016] C: Carbon is a cheap element added to steel, which can improve the hardenability and hardenability of steel. At the same time, it forms compounds with iron and various alloy elements during tempering to play the role of second phase dispersion strengthening. Therefore, adding a certain amount of carbon can effectively improve the service strength of the material. When the carbon content is lower than 0.19%, the strength of the material after quenching and tempering is difficult to reach 800MPa. When the carbon content exceeds 0.39%, the plasticity of the material will be reduced, which is not conducive to achieving the requirement of wire annealing-free through process adjustment. Therefore, the carbon content is controlled at 0.19-0.39%.
[0017] Mn: Manganese is an austenite stabilizing element, which can effectively improve the hardenability and strength. At the same time, adding a certain amount of manganese has little effect on the plasticity of steel, but manganese is easy to segregate during the solidification process of ferroalloys. Therefore, in order to ensure the strength and hardenability of the alloy, more than 0.60% manganese needs to be added. However, in order to avoid the deterioration of material uniformity caused by manganese segregation, the manganese content should be controlled below 1.45%. Therefore, the manganese content is controlled at 0.60-1.45%.
[0018] Si: Silicon replaces iron atoms in steel by substitution, hindering dislocation movement, and can significantly improve the strength of the ferrite phase. A higher silicon content will increase the hardness of the material after annealing, which is not conducive to reducing the hot-rolled strength through process adjustment, and will reduce the life of the forming mold. At the same time, a higher silicon content will reduce the low-temperature impact toughness of the steel. Therefore, the present invention controls the silicon content to ≤0.25%.
[0019] Cr: It has the effect of improving the hardenability of ferroalloys, and at the same time, it precipitates fine dispersed carbide particles during the tempering process, plays a role of dispersion strengthening, and improves the strength of the material. Chromium also has the effect of refining the structure. Therefore, in the present invention, in order to exert the solid solution strengthening and precipitation strengthening effects of chromium and improve the material structure at the same time, the chromium content is controlled to be 0.05-0.99%.
[0020] Manganese and chromium are both carbide-forming elements. To ensure good quenching performance of the material, the total amount of the two elements should be above a certain content, so that the austenite of the material is more stable during quenching and the hardenability is improved. At the same time, both can improve the final performance of the material by solid solution in the ferrite mass and forming carbides. In the design of the present invention, the sum of the content of manganese and chromium is not less than 1.10%.
[0021] Ti: Titanium easily forms compounds with carbon and nitrogen in steel. The formation temperature of titanium nitride is above 1400°C. It usually precipitates in the liquid phase or delta ferrite to achieve the purpose of refining austenite grains. Since nitrogen easily combines with boron to form boron nitride, boron loses its function of improving hardenability. The addition of titanium can combine with nitrogen with a stronger binding force to avoid the formation of boron nitride, thereby protecting boron. If the titanium content is too high, coarse titanium nitride will precipitate, resulting in reduced impact and fatigue properties of the steel. During the tempering process, if the titanium content is too high, the fluctuation amplitude of the low-temperature impact energy will increase. Therefore, the titanium content in the present invention is controlled at 0.01-0.15%.
[0022] B: Boron can change the solidification process and cast structure of steel during steelmaking, react with molten steel to form fine particles, and become non-spontaneous nucleation cores in the solidification process, reduce nucleation work, and increase nucleation rate; at the same time, boron is a surface active element in steel, which is easily adsorbed on the surface of solid crystal nuclei, hindering the supply of atoms required for crystal growth and hindering crystal growth. At the same time, boron can greatly improve the hardenability of steel. Boron can refine the cast structure, reduce dendrite segregation and regional segregation, improve the uniformity of steel, and improve hardenability. Therefore, the present invention controls the boron content to 0.0005-0.0040%.
[0023] In terms of composition design, the present invention adopts a higher C content, adds Mn and Cr elements at the same time, and controls Mn+Cr≥1.10%; the addition of B, Ti, and N elements, due to the inevitable presence of some nitrogen elements in steel, the nitrogen elements will combine with the boron added into the steel, thereby affecting the improvement of hardenability. The addition of titanium elements can combine with nitrogen elements with a stronger binding force, and controlling Ti / N≥3.5 can avoid the formation of boron nitride, avoid the effect of boron being affected, and further improve the hardenability of the material. The obtained wire rod for fasteners has high hardenability, J11 hardenability ≥40HRC, J15 hardenability ≥33HRC, can meet the quenching requirements of 50% martensite in the core of parts with a diameter of less than M32, can be used to manufacture fasteners of grade 8.8 and above with a tensile strength of not less than 800MPa, and the fasteners produced can be used for automobiles and mechanical parts.
[0024] The present invention adopts the above-mentioned element composition design to improve the hardenability of the material, avoids the addition of elements such as Mo and V that strongly improve the hardenability, and through the subsequent controlled rolling and controlled cooling technology, it is easier to obtain wire rods with low tensile strength levels. The obtained wire rods can be directly drawn and modified, eliminating the client's time-consuming and energy-intensive annealing process.
[0025] The alloy component cost of the steel of the present invention is relatively low, and mainly adopts relatively cheap elements such as C, Si, Mn, and Al, and does not contain high-cost elements such as Mo and V, which greatly reduces the alloy cost and plays a beneficial role in cost control.
[0026] The method for manufacturing the annealing-free high-hardenability high-strength fastener wire rod of the present invention comprises the following steps:
[0027] 1) Smelting and casting
[0028] According to the above-mentioned composition, smelting, LF refining and casting into steel billets or ingots; wherein, the slag basicity is controlled at 4.0-6.5 during LF refining;
[0029] 2) Initial rolling
[0030] Reheating temperature is 1100-1200°C, holding time is 90-150min, and rolling into square billet;
[0031] 3) Wire rolling
[0032] The heating temperature of the steel billet before rolling is 960-1050°C. The steel billet is water-cooled to 780-850°C before entering the last group of rolling mills. Then, after being temperature-evened for 5-15s, it enters the last group of rolling mills. The rolling speed is 15-130m / s, the wire-winding temperature is 750-850°C, and after wire-winding, it is cooled to 680-730°C at a cooling rate of 1.5-2.5°C / s, and then cooled to room temperature at a cooling rate of ≤0.5°C / s.
[0033] Furthermore, during the smelting process, the molten steel is subjected to VD or RH vacuum refining and degassing treatment.
[0034] In the method for manufacturing the annealing-free, high-hardenability, high-strength fastener wire rod of the present invention:
[0035] In order to reduce the oxygen content of molten steel and control the inclusion content during the refining process, the slag basicity of the LF refining furnace is controlled at 4.0-6.5, and the molten steel is subjected to VD or RH vacuum refining and degassing treatment when necessary.
[0036] Billet heating temperature: The heating of the billet before rolling must ensure that the billet is heated evenly inside and outside and completely austenitized. Since the composition range of the material involved in the present invention corresponds to the complete austenitization temperature (A3 line) range not exceeding 860°C, it is necessary to ensure uniform heating within the commonly used heating time in industrial production, and the minimum heating temperature is not less than 960°C. At the same time, in order to ensure a low final rolling temperature of the billet and to ensure that the heating process does not produce severe surface decarburization and abnormal grain growth, the upper limit of the heating temperature should not exceed 1050°C.
[0037] Inlet temperature of the last group of rolling mills: The factors affecting the final wire rod strength are mainly the ferrite content in the wire rod and the thickness of the ferrite-cementite layer in the pearlite. The increase of ferrite content or the increase of the thickness of the ferrite-cementite layer in the pearlite can reduce the strength of the wire rod. According to the phase transformation starting temperature of the material composition involved in the present invention, the inlet temperature of the last group of rolling mills is set to 780-850°C. The rolling deformation is carried out below the temperature at which the material begins to undergo austenite to ferrite phase transformation, which can provide deformation storage energy for the nucleation of the ferrite phase, promote the transformation of austenite to ferrite, and increase the ferrite content in the wire rod.
[0038] In order to ensure that the internal and external temperatures of the steel billet are uniform when entering the last group of rolling mills, the steel billet is water-cooled to the final rolling temperature of 780-850℃ and then subjected to temperature equalization treatment for 5-15s before entering the last group of rolling mills. If the core and surface temperatures of the steel billet are inconsistent when entering the last group of rolling mills, it is easy to produce obvious differences in the core-surface grain size or even mixed crystals, and it is also easy to produce a hardened layer on the extreme surface. As a result, even if a low-strength wire rod is obtained, transverse surface cracking may occur during the annealing-free drawing process, resulting in scrap.
[0039] Rolling speed: The rolling speed corresponds to the speed of high-speed wire after final rolling. The rolling speed directly reflects the deformation rate during the final rolling process. Too low a deformation rate will lead to insufficient austenite deformation energy storage, which is not conducive to the phase transformation of austenite to ferrite. For hot-rolled wire rods with smaller diameters, the maximum rolling speed shall not exceed 130m / s while ensuring production efficiency; for hot-rolled wire rods with larger diameters, the rolling speed shall not be less than 15m / s while ensuring the deformation rate during final rolling.
[0040] The temperature of wire coiling: Controlling the temperature of wire coiling is to prepare for the cooling phase transformation of the material. Since the high-speed rolling process will increase the temperature of the material, controlling the temperature of wire coiling by means of water cooling or air cooling is to avoid the recrystallization of the material at the elevated temperature and the abnormal growth of the grains of supercooled austenite, and to prepare for the cooling phase transformation; the temperature of wire coiling is set at 750-850℃, which can avoid the transformation of the material to harder structures such as bainite due to supercooling.
[0041] Cooling rate after spinning: The cooling range and cooling rate after spinning determine the thickness of the ferrite-cementite lamellae in the pearlite in the wire rod. Since the temperature of spinning and coiling is the austenite-ferrite two-phase region of the material, only ferrite phase transformation occurs in this temperature range, and the pearlite phase transformation is a eutectoid transformation, which is an isothermal phase transformation process and occurs below the eutectoid temperature. The eutectoid temperature of the material composition involved in the present invention is 720°C. After the wire is coiled, it is cooled to the eutectoid temperature at a relatively fast speed and then kept warm, so that the pearlite has sufficient time to complete the phase transformation and increase the thickness of the ferrite-cementite lamellae in the pearlite, effectively reducing the strength. According to the eutectoid temperature and the pearlite phase transformation rate, the cooling rate should be controlled at 1.5-2.5°C / s before the wire temperature is cooled to 680-730°C, and the cooling rate should not be higher than 0.5°C / s thereafter, to ensure that as much austenite as possible is transformed into ferrite structure to achieve the purpose of reducing the strength of the hot-rolled wire rod.
[0042] Based on the composition design, the present invention adopts a lower rolling temperature, spinning temperature, and a segmented post-rolling cooling method to control the organization and strength of the hot-rolled wire rod, so that the obtained wire rod microstructure contains more ferrite and lower pearlite structure, and the thicker ferrite-cementite layer thickness in the pearlite makes the wire rod have high hardenability while also having lower strength, with a tensile strength of ≤650MPa. The obtained wire rod can be directly drawn and reformed, eliminating a time-consuming and energy-intensive annealing process. Therefore, the wire rod for fasteners obtained by the present invention can be used to manufacture fasteners of grade 8.8 and above without annealing, simplifying the production process of high-strength fasteners and reducing production costs.
[0043] Beneficial effects of the present invention:
[0044] 1. In terms of composition design, the present invention adopts a higher C content, adds Mn and Cr elements at the same time, and controls Mn+Cr≥1.10%; adds B, Ti, and N elements, and controls Ti / N≥3.5, further improving the hardenability of the material, so that the wire rod has a high hardenability, and can be used to manufacture fasteners for automobiles and mechanical parts of grade 8.8 and above.
[0045] 2. Based on the composition design, the present invention avoids the addition of elements such as Mo and V that strongly improve the hardenability, and adopts a lower rolling temperature, spinning temperature, and a segmented post-rolling cooling method to control the organization and strength of the hot-rolled wire rod, so that the obtained wire rod microstructure contains more ferrite and lower pearlite structure, and the thicker ferrite-cementite layer thickness in the pearlite makes the wire rod have high hardenability while also having a lower tensile strength (tensile strength ≤ 650MPa), and can be directly used for drawing and reforming without annealing, eliminating a time-consuming and energy-intensive annealing process on the client side, simplifying the production process of high-strength fasteners, improving production efficiency, and reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Optical micrograph of the wire rod obtained for Example 1 of the present invention.
[0047] Figure 2 This is a scanning electron microscope photograph of the wire rod obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with the embodiments.
[0049] The chemical compositions of the embodiments and comparative examples of the present invention are shown in Table 1, the specific process parameters are shown in Table 2, and the performance parameters are shown in Table 3.
[0050] Figure 1 and Figure 2 The optical micrograph and scanning electron microscope photograph of the wire rod obtained in Example 1 of the present invention are respectively. Figure 1 It can be seen that the microstructure of the wire rod of the present invention contains more ferrite and less pearlite, wherein the ferrite content is 65%. Figure 2 It can be seen that there is a thicker ferrite-cementite layer in the pearlite structure, and the thickness of the ferrite-cementite layer is 190 to 260 mm.
[0051] It can be seen from Table 3 that the wire rod obtained by the present invention has higher hardenability and lower tensile strength, can be directly used for drawing and modification, and can achieve direct drawing deformation without annealing, which simplifies the fastener production process, improves production efficiency, and reduces production costs.
[0052]
[0053]
[0054]
[0055]
Claims
1. A wire rod for annealing-free high-hardenability high-strength fasteners, the chemical composition mass percentage of which is: C: 0.19-0.39%, Si≤0.25%, Mn: 0.6-1.45%, Cr: 0.05-0.99%, Al: 0.010-0.035%, S≤0.005%, B: 0.001-0.004%, Ti: 0.01-0.15%, O: 0.0005-0.0030%, N: 0.001-0.007%, the rest is Fe and other unavoidable impurities, and it is also necessary to meet the following requirements at the same time: Ti / N ≥ 3.5; Mn+Cr≥1.10%; The microstructure of the wire rod for fasteners is ferrite+pearlite, the volume content of ferrite is 51-77%, and the thickness of ferrite-cementite lamellae in pearlite is in the range of 150-400nm.
2. The annealing-free, high-hardenability, high-strength fastener wire rod according to claim 1, characterized in that: The wire rod for the fastener has a hardenability of J11 ≥40HRC, a hardenability of J15 ≥33HRC, and a tensile strength of ≤650MPa.
3. The method for manufacturing the annealing-free, high-hardenability, high-strength fastener wire rod according to claim 1 or 2, characterized in that: The steps include: 1) Smelting and casting According to the chemical composition of claim 1, smelting, LF refining, and casting into a steel billet or ingot; wherein the slag basicity is controlled at 4.0-6.5 during LF refining; 2) Initial rolling Reheating temperature is 1100-1200°C, holding time is 90-150min, and rolling into square billet; 3) Wire rolling The heating temperature of the steel billet before rolling is 960-1050°C. The steel billet is water-cooled to 780-850°C before entering the last group of rolling mills. Then, after being temperature-evened for 5-15s, it enters the last group of rolling mills. The rolling speed is 15-130m / s, the wire-winding temperature is 750-850°C, and after wire-winding, it is cooled to 680-730°C at a cooling rate of 1.5-2.5°C / s, and then cooled to room temperature at a cooling rate of ≤0.5°C / s.
4. The method for manufacturing the annealing-free, high-hardenability, high-strength fastener wire rod according to claim 3, characterized in that: In step 1), the molten steel is subjected to VD or RH vacuum refining and degassing treatment during the smelting process.
Citation Information
Patent Citations
Hot-rolled low-hardness steel containing titanium and boron for high-strength fastener and production method thereof
CN103695774A
High strength boron-containing cold heading steel for fastener and preparation process thereof
CN101775546A